(untitled) (gjstudies, 2021)
The rapid integration of advanced technologies into auditing practices—includingartificial intelligence, blockchain, data analytics, and robotic process automation—hascreated a significant and widening gap between the skills taught in traditional accounting education programs and those required in modern audit environments. Thispaper investigates the multifaceted challenges accounting educators face in preparingstudents for technology-driven audits, with a particular focus on curriculum design,faculty readiness, and pedagogical approaches. We employ a mixed-methods researchdesign, combining a comprehensive survey of 150 accounting programs across NorthAmerica with in-depth interviews of 30 audit partners from leading firms and 25 accounting educators specializing in audit and information systems. Our findings revealthree primary challenges: (1) a persistent disconnect between academic curricula andrapidly evolving industry technological demands, (2) a critical shortage of faculty withboth deep accounting expertise and contemporary technical proficiency, and (3) inadequate access to scalable, realistic educational technology platforms that simulatemodern audit environments. Furthermore, we identify a novel tension between teachingfoundational accounting principles and the imperative to integrate complex technological competencies. The results demonstrate that programs which have successfullybridged this gap employ an integrated, layered pedagogical model that threads technology concepts throughout the entire accounting curriculum rather than siloing themin standalone courses. We also find that partnerships between academia and auditfirms for technology access and co-development of case materials significantly improvestudent readiness. This research contributes a new framework for evaluating and redesigning accounting education in the context of technological disruption, emphasizingthe need for continuous curriculum adaptation, faculty development in emerging technologies, and the creation of immersive, technology-rich audit simulations. The studyconcludes that without systemic changes in accounting education, the profession risksa growing competency deficit that could undermine audit quality and public trust infinancial reporting.